STRATEGI PEMERINTAH TIMOR LESTE MENDAFTARKAN TENUN TAISKE DALAM WARISAN BUDAYA TAKBENDA UNESCO - Pinto Gama, Jose Soares; Putri, Penny Kurnia; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT   T h i s research a i m s to de scribe the strategy o f the G o v ermen t of T i mo r L e ste i nregistering T a i s weavingin the l i st o f U NESCO’s I n tangible Cultural H er i tage through i ts foreign policy u sing de scriptive qualitative re search m e thods. T i m o r L e ste i s a n e wlyi ndependen t country,so there ar e still many shortscoming i n the f i e lds o f edu cation, e conomy, po litcs, social, an d culture that th e g o v er n men t need s to collaborate with m a n y countries i n the w o r ld an d with i n ternational or g a n izations. The a c tivity received encouragement from v ar i ou s international an d local or g an izations t o work together. Therefore, researchers use the framework o f t h i n k i n g about G o v e rmen t t o G o v e r nmen t as First T ra ck Diplomacy an d I n tangible Cultural H er i tage c on c ep t s i n an swering the re s ear c h issue. T h e re search found that T i m o r L e ste had a na tional i n t ere sts i n the 2011-2030 d e v e lopment strategy p lan.     K ey w or d s : T a i s Tenun,Traditional W o ven F a b r i c, Intangible Cultural Heritage,UNESCO,Timor Le ste   S trategy,Timor   Le ste   G o vernment,Track   One   Diplomacy